2006
DOI: 10.1038/sj.bmt.1705383
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-tumor effects on murine mammary carcinoma in a model of nonmyeloablative haploidentical stem cell transplantation

Abstract: Despite a slight decrease in mortality over the last decade, breast cancer still remains a leading cause of cancerrelated death in women. Although anti-tumor effects have been observed after allogeneic stem cell transplantation (SCT), this treatment is not standard care owing to graftversus-host disease (GVHD) and scarcity of suitable donors. With the aim of reducing treatment-related mortality and increasing donor availability in clinical situations, we developed a preclinical mouse model that combines nonmye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…1, groups b and c.1, respectively). In accordance with our previous results [16], tumor-induced mortality was high (88%) in the negative control group of mice that had either not been treated ( Table 1, exp. 2, group c.2) and a prolonged progression-free survival of the whole group (P = 0.01).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1, groups b and c.1, respectively). In accordance with our previous results [16], tumor-induced mortality was high (88%) in the negative control group of mice that had either not been treated ( Table 1, exp. 2, group c.2) and a prolonged progression-free survival of the whole group (P = 0.01).…”
Section: Resultssupporting
confidence: 93%
“…2b) and in our previous experiments with haploBMST [16], none of the cured mice developed a palpable tumor after infusion of the NK cell-enriched haploidentical SPL cells. Figure 2b also shows that in the four out of ten mice of experimental group c.2 that were ultimately not cured (exp.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Haploidentical-SCT (haplo-SCT) could provide an enhanced allogeneic T-cell and natural killer (NK)-cell response and augment GVT effect due to the MHC molecule disparity. Vanclee et al 8 showed in murine breast cancer model that haplo-SCT could successfully induce anti-tumor activity and provide a survival advantage compared with syngeneic transplant. Non-myeloablative haplo-HSCT was reported to induce anti-tumor activity in one patient with advanced RCC after successful engraftment, but the patient eventually developed progression of the disease 1 year after transplant.…”
Section: Introductionmentioning
confidence: 99%